Implementasi Pencatatan Laporan Keuangan Berbasis Digital pada Rumah Makan Padang Djamin - Indah Nur Salsabila; Paisal Paisal; Yesita Astarina (Jurnal Kendali Akuntansi, 2026)
This research was carried out because the manual financial recording system is still used at Padang Djamin Restaurant which is not in accordance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). This condition causes transaction recording to not be well integrated, risks causing recording errors, and makes it difficult for business owners to obtain accurate financial information for decision-making. This study aims to find out the process of preparing and implementing financial statements based on Microsoft Excel-based SAK EMKM  at Padang Djamin Restaurant. This study uses a descriptive method with a qualitative approach. Data collection techniques are carried out through observation, interviews, and documentation. The research informants consist of business owners and parties involved in financial management. Data analysis uses the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawn. The results of the study show that the financial recording system used previously is still simple and has not produced financial reports in accordance with the SAK EMKM. Through the implementation of digital-based recording using Microsoft Excel, financial statements consisting of income statements, financial position statements, and notes on financial statements have been successfully prepared. The designed system also includes a general journal, ledger, adjustment journal, and balance sheet after adjustment. The implementation of this system is able to improve recording efficiency, data accuracy, ease of preparation of financial statements, and assist business owners in managing and evaluating business financial conditions more effectively.